Three Religious-Cultural Worldviews in Noah (2014)—Hedonism, Fundamentalism, and Ecofeminism - Shapiro, Marianna Ruah-Midbar (Journal of religion and popular culture, 2020)
The article proposes an interpretative study of Darren Aronofsky’s film Noah. The film draws inspiration from various spiritual traditions ranging from shamanism to Buddhism, whilst relying heavily on Jewish midrash, and adds a layer of innovation. Our main assertion is that the film attempts to present three viewpoints on issues of religion, humanity, nature, and God—while negating two of them and preferring one. Each of the various characters and groups in the film represents one of the three stances, as the film’s protagonist must cope with the problematic nature of his worldview and revisit it. The film engages with current pivotal issues: climate change, the depletion of natural resources, materialism and hedonism, fundamentalism in both religious and environmental trends, suspicion of religious institutionalized interpretations, and gendered spiritual religious beliefs. Thus, the film Noah is a cultural product that disseminates spiritual ideas and values within mainstream culture.